Study of the process of instrumental genesis of the symbolic artifact for the exponential function - García Cuéllar , M. Sc. Daysi Julissa; Martínez Miraval, M. Sc. Mihály André (Transformación, 2024)
This article describes a study of the exponential function on students of the first semester of a private University in Lima, Peru. The research was aimed at analyzing the Instrumental genesis process of this mathematical object assisted by the use of Geogebra software. Rabardel's Instrumental Approach was used as a theoretical framework. Likewise, some notions of Artigue's Didactic Engineering were used as a methodology, focusing on a priori and a posteriori analysis. The students’ answers allowed to identify the use of schemes built and activated, while interacting with the symbolic artifact for the exponential function.  The use of Geogebra favored the instrumentalization and instrumentation of the addressed mathematical object since it allowed the students to validate their conjectures.Keywords: Mathematics instruction, mathematical concepts, algebra, didactics.
Keywords: Mathematics instruction; mathematical concepts; algebra; didactics